Spatiotemporal development of spinal neuronal and glial populations in the Ts65Dn mouse model of Down syndrome - Aziz, Nadine M. (J Neurodev Disord, 2019)
BACKGROUND: Down syndrome (DS), caused by the triplication of chromosome 21, results in a constellation of clinical features including changes in intellectual and motor function. Although altered neural development and function have been well described in people with DS, few studies have investigated the etiology underlying the observed motor phenotypes. Here, we examine the development, patterning, and organization of the spinal cord throughout life in the Ts65Dn mouse, a model that recapitulates many of the motor changes observed in people with DS. METHODS: Spinal cords from embryonic to adult animals were processed for gene and protein expression (immunofluorescence) to track the spatiotemporal development of excitatory and inhibitory neurons and oligodendroglia. Postnatal analyses were focused on the lumbar region due to the reflex and gait abnormalities found in Ts65Dn mice and locomotive alterations seen in people with DS. RESULTS: Between embryonic days E10.5 and E14.5, we found a larger motor neuron progenitor domain in Ts65Dn animals containing more OLIG2-expressing progenitor cells. These disturbed progenitors are delayed in motor neuron production but eventually generate a large number of ISL1+ migrating motor neurons. We found that higher numbers of PAX6+ and NKX2.2+ interneurons (INs) are also produced during this time frame. In the adult lumbar spinal cord, we found an increased level of Hb9 and a decreased level of Irx3 gene expression in trisomic animals. This was accompanied by an increase in Calretinin+ INs, but no changes in other neuronal populations. In aged Ts65Dn animals, both Calbindin+ and ChAT+ neurons were decreased compared to euploid controls. Additionally, in the dorsal corticospinal white matter tract, there were significantly fewer CC1+ mature OLs in 30- and 60-day old trisomic animals and this normalized to euploid levels at 10–11 months. In contrast, the mature OL population was increased in the lateral funiculus, an ascending white matter tract carrying sensory information. In 30-day old animals, we also found a decrease in the number of nodes of Ranvier in both tracts. This decrease normalized both in 60-day old and aged animals. CONCLUSIONS: We show marked changes in both spinal white matter and neuronal composition that change regionally over the life span. In the embryonic Ts65Dn spinal cord, we observe alterations in motor neuron production and migration. In the adult spinal cord, we observe changes in oligodendrocyte maturation and motor neuron loss, the latter of which has also been observed in human spinal cord tissue samples. This work uncovers multiple cellular perturbations during Ts65Dn development and aging, many of which may underlie the motor deficits found in DS.